Enhancing maternal toddler parenting competence through nurturing care videos - Haryanti, Fitri; Lusmilasari, Lely; Madyaningrum, Ema; Hasanah, Nisa Nur; Amiatun, Anisa Nurul (Universitas Muhammadiyah Purwokerto, 2023)
Background: Despite increased global attention to early childhood development, children under 5 in low- and middle-income countries face heightened risks of poor developmental outcomes. In Indonesia, where innovative approaches to nurturing care are needed, video-based interventions show promise.Purpose: This study aimed to elevate maternal competence in parenting and contribute to the holistic development of children aged 0-3 years through video-based nurturing care education.Method: Non-equivalent quasi-experimental design with pre-post-test control groups was employed. This study used a consecutive sampling technique on 89 mothers with children 0-3 years old (intervention group = 40 and control group = 49). The intervention group was given health education using videos via a WhatsApp link, and the control group was given leaflets directly. Data was collected from May to August 2022, four weeks before the intervention (pre-test) and two weeks after the video and leaflets were given (post-test). The instrument was modified from the Knowledge, Attitude, and Practice (KAP) questionnaire developed by UNICEF. The effect of education was analyzed using Wilcoxon and independent t-test.Results: The group that received the intervention showed a notable and positive influence on their knowledge, attitudes, and practices (KAP levels) in contrast to the control group. This suggests the video-based intervention effectively enhanced participants' understanding, attitudes, and caregiving practices.Conclusion: The research emphasizes the positive outcomes of video-based nurturing care intervention for mothers with children aged 0-3 years. The intervention significantly improved maternal attitudes toward parenting, caregiving behaviors, and overall child development. These results emphasize the significance of employing video interventions to encourage effective nurturing care practices.